Improvising and muddling through: transnational government networks and security cooperation between Mexico and the US - Payan Alvarado, Luis Antonio (2020)
For the last 20 years, the US–Mexico security cooperation relationship has relied on transgovernmental networks (TGNs). TGNs have both substituted for the absence of more formally institutionalized cooperation and also served to implement and complement broader top-down understandings on binational collaboration. They bring great flexibility to dealing with constantly changing issues. But they are also no substitute for institutionalized cooperation. This paper argues that, while TGNs present a network model of binational cooperation and give extraordinary legs to binational work, they remain excessively dependent on the will and ability of individuals to create them and maintain them. As a result, binational cooperation remains vulnerable to personality variables as well as changing political winds.